Direct development in some Australopapuan microhylid frogs of the genera Austrochaperina, Cophixalus and Oreophryne (Anura: Microhylidae) from northern Australia and Papua New Guinea - Anstis, Marion; Parker, Fred; Hawkes, Tim; Morris, Ian; Richards, Stephen J. (Zootaxa, 2011)
Embryonic development in fifteen Australopapuan microhylid frogs of the genera Austrochaperina, Cophixalus and Oreophryne is described. These frogs have direct development during which the embryo develops to a minute froglet within the jelly capsule. Development of the operculum, presence of external gills, tail structure, gut development and timing of forelimb emergence are described and compared with the direct-developing eleutherodactylid Eleutherodactylus coqui from Puerto Rico and three Australian myobatrachid genera with direct development (Arenophryne, Metacrinia and Myobatrachus). We comment on those differences that likely reflect examples of convergent and divergent evolution and heterochrony.